Heterosynaptic long‐term depression mediated by ATP released from astrocytes. Issue 2 (8th October 2012) - Chen, Jiadong; Tan, Zhibing; Zeng, Li; Zhang, Xiaoxing; He, You; Gao, Wei; Wu, Xiumei; Li, Yuju; Bu, Bitao; Wang, Wei; Duan, Shumin
Abstract Heterosynaptic long‐term depression (hLTD) at untetanized synapses accompanying the induction of long‐term potentiation (LTP) spatially sharpens the activity‐induced synaptic potentiation; however, the underlying mechanism remains unclear. We found that hLTD in the hippocampal CA1 region is caused by stimulation‐induced ATP release from astrocytes that suppresses transmitter release from untetanized synaptic terminals via activation of P2Y receptors. Selective stimulation of astrocytes expressing channelrhodopsin‐2, a light‐gated cation channel permeable to Ca2+, resulted in LTD of synapses on neighboring neurons. This synaptic modification required Ca2+ elevation in astrocytes and activation of P2Y receptors, but not N‐methyl‐D‐aspartate receptors. Furthermore, blocking P2Y receptors or buffering astrocyte intracellular Ca2+ at a low level prevented hLTD without affecting LTP induced by SC stimulation. Thus, astrocyte activation is both necessary and sufficient for mediating hLTD accompanying LTP induction, strongly supporting the notion that astrocytes actively participate in activity‐dependent synaptic plasticity of neural circuits. © 2012 Wiley Periodicals, Inc.